Visible light-driven photocatalytic hydrogen production using Cu-doped SrTiO3 - Tolod, Kristine R. (2011)
The world's current unsustainable energy mix along with the environmental drawbacks of burning fossil fuels prompted studies for the identification of sustainable alternative and renewable energy sources. Photocatalytic water splitting is one promising solution to this problem because it permits the conversion of solar energy to chemical energy in the form of hydrogen gas. This utilized the synthesized Cu-doped SrTiO₃ photocatalysts loaded with Pd to effect the photocatalytic hydrogen production from water. The photocatalytic activity was assessed based on the characterization of the photocatalysts and the effect of varying together the calcination temperature, amount of Cu dopant and photocatalyst loading. It was determined that the amount of hydrogen evolved was largely dictated by the amount of Cu dopant present in the photocatalysts. The created Box Behnken Design optimization scenarios suggested the condition 850̊C-0.01 Cu/Sr -0.33g loading as the optimal condition for maximum hydrogen production holding all studied factors in range and the condition 850̊C - 0.01 Cu/Sr - 0.21g loading as the optimal condition for the maximum hydrogen production while minimizing Cu dopant and photocatalyst loading.
Thesis (M.S. Energy Engineering)--University of the Philippines, Diliman.
Keywords: Photocatalysis; Water -- Purification -- Photocatalysis; Strontium Titanate